100 more things every designer needs to know about people - Weinschenk, Susan (Berkeley, CA : Peachpit Press, 2020)
"Thousands of designers, marketers, and product managers have come t o rely on Susan Weinschenk's original 100 Things Every Designer Needs T o Know About People as a "go-to book" for practical advice on how to us e the latest findings in psychology and neuroscience to directly inform and improve their designs, brands, and products. Research hasn't stopp ed since the book was written, and new design challenges have emerged. Weinschenk's new book, 100 MORE Things Every Designer Needs To Know Abo ut People applies the latest research in psychology, neuroscience, brai n research, and social psychology to the design of technology products, including websites, apps, wearables, and artificial intelligence."--pr ovided by publisher.
How people see -- How people think and remember -- How people decide -- How people read and interpret information -- How people are influen ced by stories -- How people relate to other people and to technology - - How creativity influences design -- How people's bodies affect design -- How people show and buy -- How generations, geography, and gender i nfluence design -- How people interact with interfaces and devices.
Includes bibliographical references (pages 257-265) and index.
Keywords: Design -- Psychological aspects